Enhancing educational quality during MBKM implementation - Bariyyah, Khairul; Soejanto, Laily Tiarani; Latifah, Leny; Wulan Sari, Eva Kartika; Ifdil, Ifdil (Jurnal Konseling dan Pendidikan, 2023)
This study aimed to evaluate the educational quality of Merdeka Belajar-Kampus Merdeka (MBKM) curriculum, alongside the competency of students and the satisfaction level of the framework partners. An exploratory and descriptive approach was employed, involving students and partners associated with MBKM during the semester 2021/2022 academic session. A descriptive quantitative approach was also used, involving a total of 199 respondents selected through complete sampling. This group comprised 189 students, with 3 university associates, and 8 non-university partners. Data collection was carried out using a questionnaire provided by the Indonesian Ministry of Education, Culture, Analysis, and Technology, and subjected to simple regression analysis. The results showed that MBKM implementation met the quality standards encompassing education, array, community engagement, and additional criteria as specified in SN-DIKTI. This indicated a positive connection between the competency of students and the satisfaction of MBKM partners. Therefore, this study observed that MBKM implementation successfully achieved the education quality criteria for graduate competency.